The Study Of Madurese Social Dialect - Rohaniyah, Jaftiyatur (Universitas Islam Madura, 2016)
The Madurese people are originally indigenous to the island of Madura, located in the Java Sea just north of East Java, and Madura is part of the province of Jawa Timur (East Java) which contains four cities in it; Bangkalan, Sampang, Pamekasan and Sumenep. Madurese language plays important roles in maintaining and developing Indonesian language. There are at least two major roles of Madurese language. The roles are; (1) the existence of Madurese language can be used as a shield of Indonesian language against the invasion of foreign languages, and (2) Madurese language can be functioned as a vocabulary donor of Indonesian language. Madurese language is interested to be analyzed because of its unique language features. Madurese has their own rules to arrange a proper conversation politely, just like Javanese and the other culture. They have their speechlevels engaged to social dialect that used in daily communication. It is because of some factors. This social dialect and its factors of Madurese language is discussed in this research.